(untitled) (The International Journal for Scientific Research, 2024)
The Kingdom of Saudi Arabia is aiming to diversify sources of income, develop the infrastructure of the maritime sector, and enhance interconnection with all transport sectors in the Kingdom; especially that more than 75% of maritime trade is non-oil; the most recent regulated division between the transportation divisions is the Sea Transportation. Until recently, Saudi Arabia was part of some of the international treaties and conventions that are related to the marine sector, and no local laws and regulations were enforced -except for some provisions which are part of laws and regulations that regulate other matters-. That said, the local maritime laws and regulations in the Kingdom of Saudi Arabia were recently issued, and there is some un-clarity and ambiguity regarding the framework that determines the responsibilities of different stakeholders involved in a commercial accident when such an accident occurs on the regional water of the Kingdom of Saudi Arabia. The issue becomes more important when a ship which is not registered or does not hold the Saudi Flag is involved in such an accident. The ambiguity of the framework makes the application of the law complicated, and accommodates negative impacts related to -without limitation-: the time consumed while removing the accident and its effects, the environmental impact on the sea, and decreasing the cost of removing or resolving such accident. The research aims to study the challenges and gaps related to the legal framework of the maritime law when it comes to accidents of commercial ships at the regional water of the Kingdom and the responsibilities of the stakeholders. The research will use the historical and descriptive-analytical doctrinal research methodology. The researcher will find where there is a room to adapt or amend regulations that might help in resolving, seizing, or covering the current gaps and challenges related to the current regulatory framework of the regional sea of Saudi Arabia attributed to the commercial marine accidents.